The research of main measures for inhibition of growth of drug prices in the countries of European Union - Khaliq, R. N.; Yakovleva, O. S.; Яковлева, Ольга Станіславівна (Запорізький державний медичний університет, 2018)
Recently, the global pharmaceutical market has seen a steady trend towards rising drug prices. Measures to regulate the price system for medicines are being implemented in different countries in order to increase their accessibility for the population. In addition, international organizations particularly the European Commission, the International Monetary Fund are pressing the governments of Central Europe to reduce the cost of medicines. The analysis of available data allowed us to establish that in the EU countries the following containment measures are used to control the growth of drug prices: reference prices, international (external) prices and pricing based on the therapeutic value of the drug. Among the abovementioned pricing methods, the use of reference prices or pricing based on external prices is already being used by EU countries to ensure the availability of medicines for the population. The most problematic approach is pricing based on value-based pricing.
Keywords: тези доповідей